FRI0250 Anca positivity in scleroderma patients identifies a poor prognosis: Myocarditis and survival. (23rd January 2014) - Berardi, G.; De Luca, G.; Laria, A.; Bocci, M.; Rucco, M.; Capacci, A.; Correra, M.; Gigante, M.R.; Galiano, N.; Bosello, S.L.; Ferraccioli, G.
Abstract : Background: Previous studies have shown that about 7% of unselected systemic sclerosis (SSc) patients are positive for ANCA 1 . Some case reports have also described an ANCA–associated vasculitis in SSc patients with progressive renal and lung function deterioration and poor outcome. Objectives: To evaluate the prevalence of ANCA positivity in a SSc cohort and to study its association with clinical characteristics, major organ involvement and risk of mortality. Methods: We evaluated the positivity and the levels of p- and c-ANCA in our cohort of 294 SSc patients according with age, immunological characteristics, disease duration and clinical manifestations. Only patients with almost two positive ANCA assessments have been considered ANCA positive. Specifically we evaluated the presence of digital ulcers, glomerulonephritis, myositis and myocarditis. Myocarditis was defined as the presence of increasedcardiac enzymes associated with the presence of enhancement at late gadolinium-enhanced cardiac magnetic resonance imaging and/or myocarditis on myocardial biopsy. The mortality in the last 12 years was also recorded. Results: 17 patients out of 294 (5.8%) of the entire SSc cohort were identified as ANCA-positive. Six patients (35.3%) were c-ANCA positive with a mean level of 70.4±50.7 U/ml, while 11 patients (64.7%) were p-ANCA positive with a mean level of 65.8±47.7 U/ml. Out of the 17 ANCA positive patients, 58.8% presented anti-topoisomerase antibodies, 41.2% anticentromere antibodies. Sixteen patients (5.4%) presented myocarditis which was more frequent in patients with ANCA positivity than in ANCA negative patients (41.7% vs 3.2%, p<0.0001). Overall mortality was 6.8%. Mortality in ANCA positive patients was higher than in ANCA negative patients (29.4% vs 5.4%, p=0.003). There was no association between ANCA positivity and complement consumption, glomerulonephritis, myositis and digital ulcers. Conclusions: The prevalence of ANCA positivity in our cohort was 5.8% and, as previously reported, the majority of patients was positive for anti-topoisomerase antibodies. ANCA positivity was associated with myocarditis and with an increased risk of mortality. Considering the high mortality associated with cardiac involvement in SSc patients, our preliminary data suggest that ANCA positivity in SSc patients should be a warning biomarker to identify patients at risk of myocarditis and of a poor survival. References: Akimoto S, Ishikawa O, Tamura T, Miyachi Y. Antineutrophil cytoplasmic autoantibodies in patients with systemic sclerosis. Br J Dermatol 1996;134(3):407-10. Disclosure of Interest: None Declared